Corpo deseducado: gênero, performance e política do corpo em poéticas visuais - Marques, Roberta Letícia Pereira (2014)
The theoretical-poetics research described here addresses the uneducated female body as a political resistance against the institutional regulatory bodies. Through the creation of the performance "Pagando Calcinha" and its visual and audiovisual records are addressed, directly or indirectly, issues related to gender performativity, regulatory circuits of the female body and its profanation, and the body as an support and object of art, photography and records video as artistic action and as autonomous works, among other things, seeking to understand the extensive field of discussion on the topic. In discussion about your goals, seek verification of the emergence of the body as a subject of study in the field of integrated arts in the twentieth century with focus on the production of women artists from the second half of the last century; understanding the concepts of standardization, discipline and endurance in Michel Foucault and profanation in Giorgio Agambem. Searching also research of technical, conceptual and aesthetic specificities of photography and video as documentary records of performance; and also the analysis of the formal, contextual and conceptual aspects of artworks and cultural artifacts related to the political and discursive body and the body arts (performance and body art). The methodology is the Visual Poetics Research / Research in Art, guided by creative path through the approach of the art object from a reflection on the process of creation. In this sense, the research focused around the art-making as a source of practical discussion, seeking trials and developments in poetic production through hybrid languages.